Environmental Worldview of Biology Education Students: A Quantitative Assessment Across Gender and Learning Styles - Muhammad Syamsussabri; Nurmaningsih (Journal of Educational Studies, 2026)
Since environmental problems have reached a global level, it is important to determine reasons for people treating the environment badly. The New Ecological Paradigm Scale or the revised New Environmental Paradigm (NEP) Scale is an instrument used to measure environmental worldview. This study aimed to assess the environmental worldview of Biology education students using the New Ecological Paradigm Scale and see the differences in terms of gender and learning style. This research is included in a cross-sectional study (N = 170). The sample consisted of 143 females (84%) and 27 males (16%) distributed across three learning styles: visual, auditory, and motor, conducted among Biology education students in West Nusa Tenggara. Samples were taken using a cluster sampling design. The study utilized an adopted 15-item version of the revised NEP Scale (Dunlap et al., 2000), consisting of 8 positive and 7 negative statements rated on a 5-point Likert scale, with its validity and reliability statistically verified prior to the main survey. Data analysis was performed using ANOVA. The overall mean score for the New Ecological Paradigm Scale in this study was 59, which indicated a moderate environmental worldview. Descriptively, female students obtained a mean score of 58.5. Meanwhile, regarding learning modalities, students with visual, auditory, and motor learning styles all exhibited a uniformly moderate environmental worldview, with their respective mean scores tightly clustering within a narrow range of 58 to 59. Consequently, the ANOVA analysis confirmed that there are no statistically significant differences in the environmental worldview based on either gender (p = 0.953) or specific learning style categories (p = 0.781). This study revealed an overall moderate NEP response in undergraduate biology education students and identified specific areas where environmental education could play a role.